Effectiveness of an educational intervention targeting homophobic language use by young male athletes: a cluster randomised controlled trial. (10th February 2023) - Denison, Erik; Faulkner, Nicholas; O'Brien, Kerry S; Jeanes, Ruth; Canning, Mitch
Abstract : Objective: Homophobic language is common in male sport and associated with negative physical and mental health outcomes for all sport participants, but particularly for gay or bisexual youth populations. Evidence-based interventions are needed to reduce such language and mitigate harm. This study evaluated the effectiveness of a short social-cognitive educational intervention delivered by professional rugby union players in youth sport. Methods: In a two-arm, cluster randomised controlled trial, 13 Australian youth rugby teams from 9 clubs (N=167, ages 16–20, mean 17.9) were randomised into intervention or control groups. Professional rugby players delivered the intervention in-person. Frequency of homophobic language use was measured 2 weeks before and 2 weeks after the intervention. Hypothesised factors underpinning homophobic language were also measured, including descriptive (other people use), prescriptive and proscriptive injunctive norms (approval/disapproval by others), and attitudes towards the acceptability of homophobic language. Results: At baseline, 49.1% of participants self-reported using homophobic language in the past 2 weeks and 72.7% reported teammates using homophobic language. Significant relationships were found between this behaviour and the hypothesised factors targeted by the intervention. However, generalised estimating equations found the intervention did not significantly reduce homophobic language, or alter the associated norms and attitudes, relative to controls. Conclusion: Use of professional rugby athletes to deliver education on homophobic language was not effective. Other approaches to reduce homophobic language (and other forms of discrimination) such as peer-to-peer education, and enforcement of policies prohibiting specific language by coaches, should be explored.